Adhesion inhibitor composition for unvulcanized rubber and use thereof

The anti-adhesive composition for unvulcanized rubber, featuring a silicate and iron compounds with specific ratios, addresses sedimentation and adhesion issues, resulting in improved dispersibility and adhesion prevention.

JP2025038024AActive Publication Date: 2025-03-18MATSUMOTO YUSHI SEIYAKU CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024215087
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2041-01-22

AI Technical Summary

Technical Problem

Existing anti-adhesive agents for unvulcanized rubber suffer from sedimentation issues when using inorganic powders, leading to decreased productivity and poor adhesion prevention.

Method used

An anti-adhesive composition comprising a silicate, iron oxide, and iron sulfide, with a specific weight ratio, combined with anionic and nonionic surfactants in a specific ratio, to enhance dispersibility and adhesion prevention.

Benefits of technology

The composition achieves excellent dispersibility and adhesion prevention, improving workability and reducing defects in rubber products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038024000001
    Figure 2025038024000001
  • Figure 2025038024000002
    Figure 2025038024000002
  • Figure 2025038024000003
    Figure 2025038024000003
Patent Text Reader

Abstract

To provide: an adhesion inhibitor composition for unvulcanized rubber, having excellent dispersibility and adhesion inhibition property at the same time; and a method for producing unvulcanized rubber which has been subjected to an adhesion inhibition treatment performed by using the adhesion inhibitor composition for unvulcanized rubber.SOLUTION: Provided is an adhesion inhibitor composition for unvulcanized rubber, comprising: an inorganic component containing a silicate as an essential ingredient; and a surfactant. The silicate contains at least one selected from iron oxide and iron sulfide, and a total of weight ratios of the iron oxide and the iron sulfide relative to a total of the silicate, the iron oxide, and the iron sulfide is 10 wt% or less. The surfactant contains an anionic surfactant (A) and a nonionic surfactant (B), and a weight ratio (A / B) represented by [weight of (A)] / [weight of (B)] is 1 to 20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an anti-adhesive composition for unvulcanized rubber and its use. [Background technology]

[0002] In the production and processing of rubber products, unvulcanized rubber is sometimes stored in piles until it is moved on to the next process, such as molding or vulcanization. In this case, anti-adhesion agents (anti-sticking agents) are used to prevent the rubber from sticking together. Anti-adhesive agents containing inorganic powders and surfactants as their main components are widely used, and are generally applied to the rubber surface in the form of an aqueous dispersion and then dried. The application method can be spraying the aqueous dispersion or immersion in the aqueous dispersion. However, the sediment that forms when using these aqueous dispersions of inorganic powders can cause problems, such as a deterioration of the work environment and reduced productivity. If a large amount of sediment forms, the equipment must be cleaned, and the spray clogs and uneven dispersion concentration can hinder uniform application. For these reasons, there is a need for an anti-adhesion agent that produces less sediment and has excellent anti-adhesion performance.

[0003] Although various anti-adhesion agents have been developed so far, there is no anti-adhesion agent that can solve the above problems and also has sufficient anti-adhesion properties. Patent Document 1 discloses an anti-adhesive agent that contains bentonite containing a specific amount of montmorillonite, a water-swellable inorganic powder, and a surfactant containing an anionic surfactant and a nonionic surfactant in a specific ratio. By increasing the blending ratio of the nonionic surfactant compared to the blending ratio of the anionic surfactant, the adhesion of the anti-adhesive agent to the rubber surface is improved, thereby improving anti-adhesive properties. However, when the dispersion liquid is low in concentration, the dispersing effect of the anionic surfactant on the inorganic powder is significantly reduced, resulting in a problem of easy sedimentation. Patent Document 2 discloses a method for preventing adhesion by applying to the rubber surface a composition in which a fatty acid soap, a metal soap, and a specific surfactant, each having a limited number of carbon atoms and metal ions, are dispersed in water. Because no inorganic powder is used, the problem of sediment does not occur, but to achieve a sufficient adhesion prevention effect, a high concentration is required, which can cause a problem of deteriorating the physical properties of the vulcanized rubber, limiting the method of use and making it less versatile. As described above, various anti-adhesion agents have been developed, but none of them are capable of suppressing the sedimentation of inorganic powders and providing sufficient anti-adhesion properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-213202 [Patent Document 2] Japanese Patent Application Publication No. 49-18780 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide an anti-adhesive composition for unvulcanized rubber that is excellent in both dispersibility and anti-adhesive properties, and a method for producing anti-adhesive treated unvulcanized rubber using the anti-adhesive composition for unvulcanized rubber. [Means for solving the problem]

[0006] As a result of extensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by an anti-adhesive composition in which the weight ratio of the iron oxide and the iron sulfide to the total weight of silicate, iron oxide, and iron sulfide is within a specific range, and the anionic surfactant (A) and the nonionic surfactant (B) are contained in a specific ratio.

[0007] That is, the adhesion preventive composition for unvulcanized rubber of the present invention is an adhesion preventive composition for unvulcanized rubber containing an inorganic component and a surfactant, wherein the inorganic component essentially contains a silicate and at least one selected from iron oxide and iron sulfide, the total weight ratio of the iron oxide and the iron sulfide to the total of the silicate, the iron oxide and the iron sulfide is 10% by weight or less, the surfactant contains an anionic surfactant (A) and a nonionic surfactant (B), and the weight ratio (A / B) expressed as the weight of (A) / the weight of (B) is 1 to 20.

[0008] It is preferable that the composition further contains a carbonate and / or a metal soap. The anionic surfactant (A) preferably includes a fatty acid soap.

[0009] The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a treatment step of adhering the above-mentioned adhesion-preventive agent composition for unvulcanized rubber to the surface of molded unvulcanized rubber. [Effects of the Invention]

[0010] The anti-adhesive composition for unvulcanized rubber of the present invention is excellent in dispersibility and anti-adhesiveness. Furthermore, in the method for producing unvulcanized rubber of the present invention, the anti-adhesive composition for unvulcanized rubber of the present invention is used, and therefore the excellent dispersibility and anti-adhesive properties improve workability and reduce defects in rubber products. DETAILED DESCRIPTION OF THE INVENTION

[0011] [Anti-adhesion agent composition for unvulcanized rubber] The anti-adhesive composition for unvulcanized rubber of the present invention is an anti-adhesive composition for unvulcanized rubber that contains an inorganic component essentially containing a silicate, and a surfactant. Each component will be described in detail below.

[0012] [Inorganic components] The inorganic component is a component of a material that forms a coating on the surface of unvulcanized rubber to exhibit adhesion prevention properties. The anti-adhesive composition for unvulcanized rubber of the present invention contains silicate as an essential inorganic component. Silicates generally have a structure formed by connecting silica tetrahedra, each of which is formed by a triangular pyramid formed from four oxygen atoms and one silicon atom filling the gap in the middle. Silicates are further classified into nesosilicates, solosilicates, cyclosilicates, inosilicates, phyllosilicates, tectosilicates, etc., depending on the connecting method of the silica tetrahedra. In the anti-adhesive agent for unvulcanized rubber of the present invention, one or more of these silicates may be used in combination.

[0013] Nesosilicates are classified as independent interlocking silicates (SiO4) 4- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include olivines such as forsterite, fayalite, and manganese olivine; humite; garnets such as pyrope, almandine, spessartine, grossular, andradite, and uvarovite; and gadolinites such as datolite and sillimanite, and the like, and these may be used alone or in combination of two or more. Solosilicates are classified as complex interlocking silicates (Si2O7) 6- and (SiO 16 ) 12- The basic composition is at least one selected from the structures represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include epidote such as zoisite and clinozoisite, melilite such as akermanite and gehlenite, and pumpellyite such as vesuvianite, and one or more of these may be used in combination.

[0014] Cyclosilicates are classified as ring-linked silicates (Si3O9) 6- , (SiO 12 ) 8- , (SiO 18 ) 12- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include benitoite, beryl, beryl, tourmaline such as serrata, magnesite, and sphalerite, and osumilite, and these may be used alone or in combination of two or more. Inosilicates are classified as single-chain silicates (Si2O6) 4-, (Si3O9) 6- , (SiO 11 ) 6- , (SiO 15 ) 10- , (SiO 21 ) 14- The inosilicate has a basic composition having a structure represented by the chemical formula: There are no particular limitations on the inosilicate, and examples thereof include pyroxenes such as diopside, clinoenstatite, enstatite, acmite, and spodumene; and amphibole such as anthophyllite, tremolite, glaucophane, and rhodonite; and these may be used alone or in combination of two or more.

[0015] Phyllosilicates are classified as layer-connected silicates and have a basic structure represented by the chemical formula SiO2. The phyllosilicates are not particularly limited, but examples thereof include smectites such as montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite; vermiculites such as di-vermiculite and tri-vermiculite; kaolinites such as halloysite, kaolin, endelite, dickite, nacrite, and chrysotile; talc; mica such as tetrasilylic mica; pyrophyllite; margarite; clintonite; mica minerals such as muscovite, biotite, phlogopite, synthetic mica, and fluorine mica; jamonites such as paragolite, phlogopite, lepidolite, and antigorite; chlorites such as dompatite, sudoite, cookite, clinochlore, chamosite, chlorite, and nanite; and piolites-palygorskite such as sepiolite and palygorskite, and the like, and these may be used alone or in combination. Tectosilicates are classified as network-connected silicates and have a basic structure represented by the chemical formula SiO2. Tectosilicates are not particularly limited, but examples include feldspars such as sanidine, albite, anorthite, and nepheline; zeolites such as leucite, scholesite, and heulandite; and beryl, and these may be used alone or in combination.

[0016] The silicate contained in the inorganic component used in the present invention preferably contains a phyllosilicate, which can form a coating with good water dispersibility and excellent adhesion resistance. In particular, it is preferable that the phyllosilicate is at least one selected from smectite, kaolinite, talc, and mica, since this forms a coating with excellent adhesion resistance. When smectite comes into contact with water, water molecules hydrate one after another with the exchangeable cations between the layers, causing the smectite to swell, allowing it to be effectively dispersed in water. Therefore, if the phyllosilicate is smectite, it is more preferable because it has excellent dispersibility when blended in water and improves film formation. Furthermore, among smectites, montmorillonite is preferred because it has particularly remarkable water swelling properties.

[0017] Montmorillonite is a dioctahedral hydrous layered silicate mineral that contains sodium, calcium, potassium, magnesium, hydrogen ions, and other exchangeable cations. These cations are easily exchangeable and can easily absorb water. When the exchangeable cation is sodium ion, it easily absorbs water molecules due to hydration force, increasing the interlayer spacing and causing significant swelling. Generally, a layered clay mineral containing montmorillonite as a main component is called bentonite. Bentonite is an example of an inorganic component and can easily adsorb to the surface of unvulcanized rubber to form a coating. Since the bentonite coating has excellent adhesion prevention and slip properties, it is more preferable that the silicate in the anti-adhesive agent composition for unvulcanized rubber of the present invention contains bentonite as an essential component. Furthermore, if the bentonite contains sodium bentonite at a high purity, the water swelling effect is particularly pronounced, which is particularly preferable.

[0018] The amount of silicate contained in the anti-adhesive agent composition for unvulcanized rubber of the present invention is not particularly limited, but is preferably 30 to 90 parts by weight, more preferably 32.5 to 87.5 parts by weight, even more preferably 35 to 85 parts by weight, and particularly preferably 37.5 to 82.5 parts by weight, when the total amount of the inorganic components and the surfactant is 100 parts by weight. When the silicate content is 30 parts by weight or more, anti-adhesive properties tend to be improved, and when it is 90 parts by weight or less, dispersibility tends to be improved.

[0019] In addition to the silicate, the inorganic component essentially contains at least one selected from iron oxide and iron sulfide. The total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide is 10% by weight or less. Silicate may be present together with a trace amount of iron compound. However, since iron compounds have a higher specific gravity than silicate or carbonate, if the weight ratio of iron compounds in silicate exceeds 10% by weight, sedimentation occurs, resulting in poor productivity and reduced adhesion prevention. The iron compound in the present invention refers to at least one selected from iron oxide and iron sulfide, and may contain both. The total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide is preferably 9% by weight or less, more preferably 8% by weight or less, even more preferably 7% by weight or less, and particularly preferably 6% by weight or less. On the other hand, there is no particular limitation on the lower limit of the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide, but the following are preferred in order (the larger the number in parentheses, the more preferred it is): (1) more than 0% by weight, (2) 0.05% by weight, (3) 0.1% by weight, (4) 0.3% by weight, (5) 0.6% by weight, (6) 0.7% by weight, (7) 0.8% by weight, (8) 0.9% by weight, and (9) 1% by weight.

[0020] As a method for adjusting the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide, silicate containing co-existing iron compounds in an amount of 10 wt % or less can be obtained commercially, or a silicate composition containing an iron compound may be subjected to a process such as centrifugation or centrifugal separation, or an iron compound may be mixed.

[0021] [Method for analyzing the weight percentage of iron compounds] The weight percentage of iron compounds present with silicates was measured by powder X-ray diffraction. When the measured value was below the detection limit, it was taken as 0% by weight.

[0022] The inorganic component may contain an inorganic substance other than silicates, iron oxides, and iron sulfides. Examples of inorganic substances other than silicates, iron oxides, and iron sulfides include, but are not limited to, carbonates such as calcium carbonate, sodium carbonate, and magnesium carbonate; sulfates such as calcium sulfate and barium sulfate; metal oxides such as amorphous silica, alumina, magnesium oxide, antimony trioxide, titanium oxide, and white carbon; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; red iron oxide; carbon black; and graphite. Among these inorganic substances other than silicates, iron oxides, and iron sulfides, carbonates are preferred in terms of preventing adhesion of unvulcanized rubber, and at least one selected from calcium carbonate, sodium carbonate, and magnesium carbonate is more preferred.

[0023] There are no particular limitations on the average particle size of the inorganic component, but taking into consideration factors such as adhesion to unvulcanized rubber, it is preferably 0.1 to 200 μm, more preferably 0.1 to 100 μm, even more preferably 0.1 to 50 μm, particularly preferably 0.1 to 40 μm, and most preferably 0.1 to 30 μm.

[0024] [Surfactant] The surfactant is an essential component of the present invention, and is a component that aids in the dispersion of the anti-adhesive composition and in the "wetting" of the unvulcanized rubber. By including a surfactant in the anti-adhesive composition for unvulcanized rubber of the present invention, the dispersibility of the inorganic components is improved, suppressing sedimentation, and the wettability of the unvulcanized rubber is improved, allowing for a more uniform coating to be formed on the surface of the unvulcanized rubber.

[0025] The surfactant used in the present invention essentially contains an anionic surfactant and a nonionic surfactant. The anionic surfactant improves the dispersibility of the anti-adhesive composition, while the nonionic surfactant improves the adhesion of the anti-adhesive composition to rubber. Therefore, both the anionic surfactant and the nonionic surfactant are essential.

[0026] An important point in the present invention is the correlation between the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide, and the weight ratio (A / B) expressed by the anionic surfactant (A) and the nonionic surfactant (B). In other words, it was discovered that the substance that inhibits the stability of the anti-adhesive composition is an iron compound, and that when the iron compound is at a specific value, the iron compound can be adequately dispersed when the anionic surfactant (A) and the nonionic surfactant (B) are blended in a specific ratio.

[0027] That is, to satisfy both dispersibility and adhesion performance, the weight ratio (A / B) of the anionic surfactant (A) to the nonionic surfactant (B) needs to be in the range of 1 to 20. If A / B is less than 1, dispersibility decreases and sediment increases. On the other hand, if A / B exceeds 20, adhesion decreases. A / B is preferably 1.2 to 18, more preferably 1.4 to 16, and even more preferably 1.6 to 14.

[0028] There are no particular limitations on the anionic surfactant and nonionic surfactant, and one or more types may be contained. Examples of anionic surfactants include fatty acid soaps such as potassium caprate, sodium caprate, sodium laurate, potassium laurate, sodium palmitate, potassium plumitate, potassium stearate, sodium stearate, sodium palm kernel oil fatty acid, potassium palm kernel oil fatty acid, potassium palm stearate, sodium palm stearate, sodium coconut oil fatty acid, potassium coconut oil fatty acid, sodium tallow fatty acid, and potassium tallow fatty acid; alkyl sulfates such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium stearyl sulfate, and sodium cetyl sulfate; polyoxyalkylene alkyl ether acetates such as polyoxyethylene tridecyl ether sodium acetate; alkyl benzene sulfonates such as sodium dodecyl benzene sulfonate; and polyoxyalkylene alkyl ether sulfates. long-chain sulfosuccinates such as sodium dioctyl sulfosuccinate and sodium 2-ethylhexyl sulfosuccinate; N-acyl sarcosinates such as sodium oleoyl sarcosinate and sodium lauroyl sarcosinate; higher fatty acid amide sulfonates such as sodium stearoyl methyl taurate, sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, and sodium palmitoyl methyl taurate; alkyl phosphates such as sodium monostearyl phosphate; polyoxyalkylene alkyl ether phosphate esters such as sodium polyoxyethylene oleyl ether phosphate and sodium polyoxyethylene stearyl ether phosphate; long-chain N-acyl glutamates such as sodium monosodium lauroyl glutamate and disodium N-stearoyl-L-glutamate, and the like, and one or more of these may be used in combination.

[0029] Examples of nonionic surfactants include decyl ether of 3-mol polyoxyethylene, decyl ether of 3-mol polyoxyethylene and 1-mol polyoxypropylene, decyl ether of 5-mol polyoxyethylene, decyl ether of 7-mol polyoxyethylene, isodecyl ether of 3-mol polyoxyethylene and 1-mol polyoxypropylene, isodecyl ether of 5-mol polyoxyethylene, isodecyl ether of 7-mol polyoxyethylene, lauryl ether of 3-mol polyoxyethylene and 1-mol polyoxypropylene, lauryl ether of 5-mol polyoxyethylene, lauryl ether of 7-mol polyoxyethylene, tridecyl ether of 3-mol polyoxyethylene, tridecyl ether of 3-mol polyoxyethylene and 1-mol polyoxypropylene, tridecyl ether of 5-mol polyoxyethylene, tridecyl ether of 7-mol polyoxyethylene, polyoxyethylene polyoxyalkylene alkyl ethers such as isotridecyl ether of 3 moles of polyoxyethylene added, isotridecyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, isotridecyl ether of 5 moles of polyoxyethylene added, isotridecyl ether of 7 moles of polyoxyethylene added, myristyl ether of 3 moles of polyoxyethylene added, myristyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, myristyl ether of 5 moles of polyoxyethylene added, myristyl ether of 7 moles of polyoxyethylene added, cetyl ether of 3 moles of polyoxyethylene added, cetyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, cetyl ether of 5 moles of polyoxyethylene added, and cetyl ether of 7 moles of polyoxyethylene added; polyoxyalkylene alkylphenyl ethers such as polyoxyethylene nonylphenyl ether and polyoxyethylene octylphenyl ether; polyoxyalkylene fatty acid esters such as polyoxyethylene monolaurate and polyoxyethylene monooleate;Examples of such polyoxyalkylene sorbitan fatty acid esters include polyoxyethylene sorbitan monostearate and polyoxyethylene sorbitan monooleate; polyoxyalkylene alkylamines; fatty acid alkanolamides; polyoxyalkylene fatty acid amides; polyoxyalkylene hydrogenated castor oil; polyoxyalkylene sorbitol fatty acid esters; polyglycerin fatty acid esters; alkyl glycerin ethers; polyoxyalkylene cholesteryl ethers; alkyl polyglucosides; sucrose fatty acid esters; and oxyethylene-oxypropylene block polymers, and these may be used alone or in combination.

[0030] The amount of surfactant contained in the anti-adhesive agent composition for unvulcanized rubber of the present invention is not particularly limited, but when the total amount of the inorganic components and surfactant is 100 parts by weight, it is preferably 1 to 40 parts by weight, more preferably 2 to 35 parts by weight, even more preferably 3 to 30 parts by weight, and particularly preferably 4 to 25 parts by weight. If the content of surfactant is 1 part by weight or more, dispersibility tends to improve, and if it is 40 parts by weight or less, adhesion prevention tends to improve.

[0031] The anti-adhesive composition for unvulcanized rubber of the present invention may further contain the following components in addition to the components explained above.

[0032] [Metal soap] Metal soaps are components that adhere to the surface of unvulcanized rubber and can reduce friction between unvulcanized rubbers. Examples of metal soaps include magnesium laurate, calcium laurate, zinc laurate, magnesium myristate, calcium myristate, zinc myristate, magnesium palmitate, calcium palmitate, zinc palmitate, magnesium stearate, calcium stearate, zinc stearate, aluminum trioctadecanoate, aluminum dioctadecanoate, aluminum monooctadecanoate, calcium octadecanoate, zinc octadecanoate, magnesium octadecanoate, and barium octadecanoate, and one or more of these may be used in combination. As the metal soap, at least one selected from magnesium stearate, calcium stearate and zinc stearate is preferred because it is highly effective in reducing friction between unvulcanized rubbers.

[0033] Furthermore, it is preferable that the anti-adhesive composition for unvulcanized rubber of the present invention contains a carbonate and / or a metal soap in order to achieve the effects of the present invention. When the anti-adhesive composition for unvulcanized rubber of the present invention contains a carbonate and / or a metal soap, the total content of the carbonate and the metal soap is not particularly limited, but is preferably 1 to 40 parts by weight, more preferably 2 to 35 parts by weight, even more preferably 3 to 30 parts by weight, and most preferably 4 to 25 parts by weight, relative to 100 parts by weight of the total amount of the inorganic component and the surfactant. If the total content of the carbonate and the metal soap is 1 part by weight or more, dispersibility tends to improve, and if it is 40 parts by weight or less, anti-adhesiveness tends to improve.

[0034] [Water-soluble polymer] The water-soluble polymer is a component that can impart viscosity to the anti-adhesive composition for unvulcanized rubber and improve adhesion to the surface of unvulcanized rubber. This effect can be further enhanced, particularly when the composition for unvulcanized rubber is in the form of an aqueous dispersion, as described below. Examples of water-soluble polymers include starches such as oxidized starch, starch acetate, starch phosphate, carboxymethyl starch, carboxyethyl starch, hydroxyethyl starch, cationic starch, cyanoethylated starch, and dialdehyde starch; mannan; alginic acids such as alginic acid, sodium alginate, propylene glycol alginate, triethanolamine alginate, and ammonium alginate; methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and hydroxyethylmethylcellulose; Examples of suitable water-soluble polymers include cellulose ethers such as ethyl cellulose, hydroxyethyl ethyl cellulose, and carboxymethyl cellulose; natural gums such as taracant gum, gum arabic, guar gum, xanthan gum, British gum, glucomannan, gellan gum, tara gum, locust bean gum, and carrageenan; sodium polyacrylate; polyvinyl alcohol; polyethylene glycol; polyethylene oxide; water-soluble acrylic resins; water-soluble urethane resins; water-soluble melamine resins; water-soluble epoxy resins; water-soluble butadiene resins; and water-soluble phenolic resins, and these may be used alone or in combination.

[0035] [Polyhydric alcohol] Polyhydric alcohol is a component that adheres to the surface of unvulcanized rubber, imparts lubricity to the unvulcanized rubber, and reduces friction between the unvulcanized rubber. Examples of polyhydric alcohols include glycerin, 1,3-butanediol, propylene glycol, dipropylene glycol, pentylene glycol, neopentyl glycol, hexylene glycol, polyethylene glycol, erythritol, pentaerythritol, dipentaerythritol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, xylitol, sorbitol, mannitol, maltitol, maltotriose, glucose, sucrose, fructose, and maltose, and one or more of these may be used in combination.

[0036] [Antifoaming agent] Examples of the defoaming agent include silicone-based defoaming agents such as polymethylsiloxane and polyether-modified silicone; fat-based defoaming agents such as castor oil, sesame oil, linseed oil, and animal and vegetable oils; fatty acid-based defoaming agents such as stearic acid, oleic acid, and palmitic acid; fatty acid ester-based defoaming agents such as isoamyl stearate, distearyl succinate, ethylene glycol distearate, and butyl stearate; and olefin-based defoaming agents such as polyoxyalkylene monohydric alcohol di-t-amylphenoxyethanol, 3-heptanol, and 2-ethylhexanol. Examples of such antifoaming agents include alcohol-based antifoaming agents; ether-based antifoaming agents such as di-t-amylphenoxyethanol, 3-heptyl cellosolve, nonyl cellosolve, and 3-heptyl carbitol; phosphate-based antifoaming agents such as tributyl phosphate and tris(butoxyethyl) phosphate; amine-based antifoaming agents such as diamylamine; amide-based antifoaming agents such as polyalkylene amide and acylate polyamine; sulfate-based antifoaming agents such as sodium lauryl sulfate; polyoxyalkylene-based antifoaming agents; and mineral oil, and these may be used alone or in combination.

[0037] [Preservatives] Examples of preservatives include thiazoles such as thiazole and 2-mercaptothiazole; thiocyanates such as methylene bisthiocyanate and ammonium thiocyanate; sulfimides such as o-benzoic sulfimide and phenylmercuric-o-benzoic sulfimide; alkyl dialkyl thiocarbamates such as methyl dimethyl thiocarbamate and ethyl diethyl dithiocarbamate; thiuram sulfides such as tetramethyl thiuram sulfide and tetraethyl thiuram sulfide; thiuram disulfides such as tetramethyl thiuram disulfide and tetraethyl thiuram disulfide; dithiocarbamates such as ferric diethyl dithiocarbamate and lead dimethyl dithiocarbamate; sulfamides such as o-toluenesulfonamide and benzenesulfonanilide; 1-aminonaphthyl-4-sulfonic acid, 1-amino phenols such as pentachlorophenol and o-phenylphenol and alkali metal salts thereof; chloroquinones such as tetrachloro-p-benzoquinone and 2,3-dichloro-1,4-naphthoquinone; nitro group-containing compounds such as dinitrocaprylphenylcrotonate and dinitro-o-cresol; triazines such as 1,3,5-trihydroxyethylhexahydro-1,3,5-triazine and 1,3,5-triethylhexahydro-1,3,5-triazine; organic mercury compounds such as phenylmercuric phthalate and o-hydroxyphenylmercuric chloride; amines such as p-aminoazobenzene and diphenylamine; amides such as cinnamanilide; iodine-containing compounds such as 1,3-diiodo-2-propanol; and the like. These may be used alone or in combination of two or more.

[0038] 〔water〕 The anti-adhesive composition for unvulcanized rubber of the present invention may contain water, which is preferable from the viewpoint of handleability. The water may be any of tap water, ion-exchanged water, distilled water, etc., and is not particularly limited, but ion-exchanged water and distilled water are preferred. From the viewpoint of quality control, soft water is preferred because its hardness can be adjusted. When the anti-adhesive composition for unvulcanized rubber of the present invention contains water, the anti-adhesive composition for unvulcanized rubber may be in the form of an aqueous dispersion in which components other than water are dispersed or dissolved in water.

[0039] When the adhesion-preventive composition for unvulcanized rubber of the present invention is in the form of an aqueous dispersion, the weight percentage of water in the adhesion-preventive composition for unvulcanized rubber is not particularly limited, but is preferably 90 to 99.99% by weight, more preferably 92.5 to 99.95% by weight, and even more preferably 95 to 99.5% by weight. When the weight percentage of water is 90% by weight or more, drying properties tend to be improved, and when it is 99.9% by weight or less, adhesion prevention properties tend to be improved.

[0040] [Method for producing anti-adhesive agent for unvulcanized rubber] The method for producing the adhesion-preventive composition for unvulcanized rubber of the present invention is not particularly limited with respect to the mixing order, mixing equipment to be used, etc., as long as it includes a step of mixing the inorganic component, the surfactant, and, if necessary, other components, etc. The adhesion-preventive composition for unvulcanized rubber can be produced, for example, by sequentially adding and mixing the components to a mixer such as a ribbon mixer or a vertical screw mixer.

[0041] [Method for producing anti-adhesion treated unvulcanized rubber] The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber to the surface of unvulcanized rubber. Preferably, the unvulcanized rubber is one that has been molded. In the treatment step, a wet method, that is, a method using the anti-adhesive composition for unvulcanized rubber in the form of the above-mentioned aqueous dispersion, is preferred.

[0042] When the treatment step is carried out by a wet method, examples thereof include a method of spraying an anti-adhesive composition for unvulcanized rubber in the form of an aqueous dispersion, a method of spraying the rubber in a thin stream, and a method of immersing the rubber in an aqueous dispersion. The method of immersion in an aqueous dispersion is preferred because it allows the anti-adhesive composition for unvulcanized rubber to be uniformly adhered. The unvulcanized rubber used in the production method of the present invention is usually in a heated state at 100 to 180°C, and the unvulcanized rubber can be cooled by immersion in an aqueous dispersion. The temperature of the aqueous dispersion is not particularly limited, but is preferably 0 to 60°C. Next, a step of drying the unvulcanized rubber after the application of the aqueous dispersion may be carried out. The drying method is not particularly limited, but a method of forced drying by blowing hot air using a hot air blower or blow heater is preferable because it is inexpensive.

[0043] The treatment step may be carried out by a dry method, that is, a method using an anti-adhesive composition for unvulcanized rubber that does not contain water. The anti-adhesion treated unvulcanized rubber produced in this manner can be prevented from adhering to each other when stacked and stored until moving on to the next process. [Example]

[0044] The present invention will be specifically described below with reference to examples and comparative examples. The present invention is not limited to these examples. The physical properties in the examples and comparative examples were evaluated as follows.

[0045] [Adhesion resistance] An NR / BR test piece (natural rubber / butadiene rubber; thickness 0.5 cm × length 5 cm × width 3 cm) heated to 100°C was immersed in an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber (water weight ratio 98.5%) and immediately removed. Two immersed rubber test pieces were prepared, air-dried, stacked, and subjected to a pressure of 1000 kg / m 2 The test piece was placed in a 40°C thermostatic chamber under a load of 0.015 N / cm and left for 24 hours. The test piece was removed from the thermostatic chamber, cooled to room temperature, and the peel resistance (N / cm) was measured at a speed of 100 mm / min using a tensile tester. The smaller the peel resistance, the easier the peel and the higher the adhesion resistance. The evaluation criteria were as follows, and a peel resistance of less than 2 N / cm was considered to be acceptable. Peel resistance of 1N / cm or less: Excellent adhesion resistance (unvulcanized rubber can be easily peeled off from each other, ◎ is the index) Peel resistance is over 1N / cm and less than 2N / cm: Good adhesion resistance (unvulcanized rubber can be peeled off from each other without any load, index is ○) Peel resistance is 2N / cm or more and 3N / cm or less: Poor adhesion resistance (the load when peeling unvulcanized rubber is large, adhesion resistance is low, and the index is △) Peel resistance greater than 3 N / cm: Very poor adhesion resistance (rubbers adhere to each other and are difficult to peel off. Very poor adhesion resistance, index: ×)

[0046] [Dispersibility] An aqueous dispersion of the anti-adhesive composition for unvulcanized rubber (water weight ratio: 98.5%) was prepared and placed in a 100 ml measuring cylinder and allowed to stand for 24 hours. After standing, the presence or absence of precipitation was confirmed. If precipitation was present, the measuring cylinder was inverted and mixed to evaluate whether the precipitation could be redispersed. The evaluation criteria for dispersibility were as follows: No sedimentation: Dispersibility is very good (index: ◎) Sedimentation occurs, but it is easily redispersed: Dispersibility is good (number of inversions is less than 5 times, index is ○) Settling occurs and redispersion is difficult: poor dispersibility (number of inversions is more than 5 but less than 10 times, index is △) Settling occurs and redispersion is very difficult: Dispersibility is very poor (number of inversions exceeds 10 times, index is ×)

[0047] Example 1 80 g of bentonite 1, 10 g of calcium carbonate, 8 g of dioctyl sodium sulfosuccinate, and 2 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive composition for unvulcanized rubber. Next, 4.5 g of the above anti-adhesive composition was added to 295.5 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber. The resulting aqueous dispersion was evaluated for its anti-adhesive properties and dispersibility. The evaluation results are shown in Table 1, and the anti-adhesive properties and dispersibility were excellent.

[0048] (Examples 2 to 23) In Examples 2 to 23, anti-adhesive compositions for unvulcanized rubber and aqueous dispersions thereof were obtained and evaluated in the same manner as in Example 1, except that the compositions were changed as shown in Tables 1 to 3. The evaluation results are shown in Tables 1 to 3.

[0049] (Comparative Example 1) 80 g of bentonite 4, 10 g of calcium carbonate, 8 g of dioctyl sodium sulfosuccinate, and 2 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive composition for unvulcanized rubber. Next, 4.5 g of the above anti-adhesive composition was added to 295.5 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber. The resulting aqueous dispersion was evaluated for anti-adhesive properties and dispersibility. The evaluation results are shown in Table 4, and dispersibility was poor.

[0050] (Comparative Examples 2 to 8) In Comparative Examples 2 to 8, anti-adhesive compositions for unvulcanized rubber and aqueous dispersions thereof were obtained and evaluated in the same manner as in Comparative Example 1, except that the compositions were changed as shown in Table 4. The results are shown in Table 4. In the above examples and comparative examples, POE(n) means polyoxyethylene (number of repeating oxyethylene units: n), and POP(n) means polyoxypropylene (number of repeating polyoxypropylene units: n). The types of iron compounds contained in the silicate used and the weight ratio of the iron compounds to the silicate are as follows: Bentonite 1: 1% iron oxide by weight, 99% silicate by weight Bentonite 2: 2% by weight of iron oxide and iron sulfide, 98% by weight of silicate Bentonite 3: 5% by weight of iron oxide and iron sulfide, 95% by weight of silicate Bentonite 4: 10% by weight of iron oxide and iron sulfide, 90% by weight of silicate Bentonite 5: 15% by weight of iron oxide and iron sulfide, 85% by weight of silicates Bentonite 6: 20% by weight of iron oxide and iron sulfide, 80% by weight of silicate Kaolin: 0.1% by weight of iron oxide, 99.9% by weight of silicate

[0051] [Table 1]

[0052] [Table 2]

[0053] [Table 3]

[0054] [Table 4]

[0055] As can be seen from Tables 1 to 3, the anti-adhesive compositions for unvulcanized rubber of Examples 1 to 23 are anti-adhesive compositions for unvulcanized rubber containing an inorganic component and a surfactant, wherein the inorganic component essentially contains silicate and at least one selected from iron oxide and iron sulfide, the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is 10% by weight or less, the surfactant contains anionic surfactant (A) and nonionic surfactant (B), and the weight ratio (A / B) expressed as the weight of (A) / the weight of (B) is 1 to 20, and therefore the compositions achieve both excellent dispersibility and excellent anti-adhesive properties, which are the objective of the present application. On the other hand, as can be seen from Table 4, when the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide exceeds 10% by weight (Comparative Examples 1 and 2), when (A / B) is not within the range of 1 to 20 (Comparative Examples 3, 4, 5, and 6), or when silicate and at least one selected from iron oxide and iron sulfide are not contained (Comparative Examples 7 and 8), at least one of dispersibility and anti-adhesion properties, which are the issues of the present application, is not achieved. [Industrial Applicability]

[0056] The anti-adhesive composition for unvulcanized rubber of the present invention is used in the production and processing of unvulcanized rubber products, and can prevent adhesion of rubber when the unvulcanized rubber is stored in piles until it is transferred to the next process such as molding or vulcanization. In this case, the anti-adhesive composition has good dispersibility and anti-adhesive properties, making it possible to reduce defects in rubber products.

Claims

1. An anti-adhesive composition for unvulcanized rubber, comprising an inorganic component and a surfactant, The inorganic component essentially contains a silicate and at least one selected from iron oxide and iron sulfide, The total weight ratio of the iron oxide and the iron sulfide to the total weight of the silicate, the iron oxide, and the iron sulfide is 10% by weight or less, The surfactant comprises an anionic surfactant (A) and a nonionic surfactant (B), and the weight ratio (A / B) expressed as the weight of (A) / the weight of (B) is 1 to 20.

2. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, further comprising a carbonate and / or a metal soap.

3. 3. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, wherein the anionic surfactant (A) comprises a fatty acid soap.

4. A method for producing adhesion-preventively treated unvulcanized rubber, comprising a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber according to any one of claims 1 to 3 to a surface of molded unvulcanized rubber.

Citation Information

Patent Citations

  • Sticking-preventing agent for unvulcanized rubber

    JP2011144221A

  • Adhesion prevention agent for unvulcanized rubber and its utilization

    JP2017031296A

  • Adhesion preventive agent composition for unvulcanized rubber and use of the same

    JP2018100387A

  • Adhesion preventive for unvulcanized rubber and water dispersion of adhesion preventive for unvulcanized rubber

    JP2018193416A

  • Adhesion preventive composition for unvulcanized rubber and use thereof

    JP2019094455A